O estágio curricular supervisionado em espaços não escolares no curso de pedagogia da Universidade do Estado da Bahia (UNEB): as contribuições no percurso formativo - Pereira, Ana Lúcia Nunes (2017)
The aim of this research is to analyze the supervised curricular internship in non-school educational services and their contribution to teacher training. The question posed was: Which is the formative contribution that the supervised curricular internship in non-school spaces brings to the teachers in training from the pedagogy course of the State University of Bahia (UNEB)? The general objective was to investigate the formative contributions that the supervised curricular internship in non-school spaces enables to teachers in training from the pedagogy course of UNEB. The specific objectives were: to analyze the articulation between curriculum, culture and the formation in the internship in non-school educational services; to identify, in the political and pedagogical project of the pedagogy course from UNEB, the elements that define and constitute the internship in non-school educational services; to analyze if the internship in non-school educational services contributes to the formation of the students of the pedagogy course from UNEB. The theoretical reference is based on the conceptions proposed by Afonso (2014, 2001), Bauman (2012), Brandão (1995), Contreras (2013), Chizzotti and Ponce (2012), Marcelo Garcia (1999), Gohn (2013,2010), Grundy (1991), Haddad (2016), Pimenta e Lima (2004), Freire (1967, 1980, 1983, 1987, 1989, 1992, 2000, 2002, 2006, 2013), Feldmann (2014, 2009), Gimeno Sacristán (2007, 2002, 2000, 1999), Vásques (2011), Zabalza (2014). The analysis of the authors' ideas allowed understanding the context in which the supervised curricular stage develops in non-school educational services, as well to enlarge and interpret the data produced. This is a qualitative research, developed in two independent stages. The first stage was the bibliographical and documentary research. The second one was an investigation of the phenomenon, to understand the vision of the subjects involved in the formation process. Considering the importance of the data collection instruments to the process of a research, to this phase was selected the observation and the semi-structured interview as methodology. The subjects of this study were 30 training teachers and 05 Professors that coordinate the curricular internship, all of them belonging to the State University of Bahia. The results showed that the internship in non-school spaces is important to enlarge the performance of the pedagogues, as a space for the construction of training and humanization and also explained the distance between theory and practice in the development of their actions. It is expected that this research may encourage others studies in the field of the internship in non-school spaces to the teacher training